Polysaccharides Derived From the Brown Algae Lessonia nigrescens Enhance Salt Stress Tolerance to Wheat Seedlings by Enhancing the Antioxidant System and Modulating Intracellular Ion Concentration - Zou, Ping; Lu, Xueli; Zhao, Hongtao; Yuan, Yuan; Meng, Lei; Zhang, Chengsheng; Li, Yiqiang (Frontiers in Plant Science, 2019)
Soil salinity reduces plant growth and is a major factor that causes decreased agricultural productivity worldwide. Seaweed polysaccharides promote crop growth and improve plant resistance to abiotic stress. In this study, polysaccharides from brown seaweed Lessonia nigrescens (LNP) were extracted and further separated and fractionated. Two acidic polysaccharides (LNP-1 and LNP-2) from crude LNP were obtained and characterized. The latter had a lower molecular weight (40.2 kDa) than the former (63.9 kDa), but had higher uronic acid and sulfate content. Crude LNP and LNP-2 were composed of mannose, glucuronic acid, fucose and xylose, whereas LNP-1 has little mannose. Moreover, the effects on plant salt tolerance of the three polysaccharides were investigated. The results showed that crude LNP, LNP-1 and LNP-2 promoted the growth of plants, decreased membrane lipid peroxidation, increased the chlorophyll content, improved antioxidant activities, and coordinated the efflux and compartmentation of intracellular ion. All three polysaccharides could induce plant resistance to salt stress, but LNP-2 was more effective than the other two. It can be concluded that both molecular weight and sulfate degree contribute to salt resistance capability of polysaccharides derived from L. nigrescens.